2020
DOI: 10.1002/jlb.4mr0820-011r
|View full text |Cite
|
Sign up to set email alerts
|

Brief review on the roles of neutrophils in cancer development

Abstract: Neutrophils, which are traditionally regarded as a hallmark of inflammation, are also a member of the intratumoral immune cells. The roles of neutrophils in cancer development are diverse and undefined. So far, they are known to be involved in tumor initiation and tumor cell proliferation and metastasis. They show heterogeneity in both phenotypes and functions during early versus late stage of cancer development. Because they are also associated with the clinical outcomes of various types of solid tumors, canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 109 publications
(184 reference statements)
0
15
0
Order By: Relevance
“…Reduced immune recognition, increased tumour cell survival, or development of an immunosuppressive tumour microenvironment (TME) contribute to the tumour escape stage [9]. The TME establishment is a slow process, and recent studies showed that the early-and late-stage TMEs of multiple cancers have cells with different cell heterogeneity and functions [10][11][12][13][14]. Recent advances in multi-omics and single-cell RNA sequencing (scRNA-seq) techniques have contributed significantly to the characterisation of TME, which have resulted in the discovery of more cell types and their response to therapies [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced immune recognition, increased tumour cell survival, or development of an immunosuppressive tumour microenvironment (TME) contribute to the tumour escape stage [9]. The TME establishment is a slow process, and recent studies showed that the early-and late-stage TMEs of multiple cancers have cells with different cell heterogeneity and functions [10][11][12][13][14]. Recent advances in multi-omics and single-cell RNA sequencing (scRNA-seq) techniques have contributed significantly to the characterisation of TME, which have resulted in the discovery of more cell types and their response to therapies [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have also demonstrated the prognostic value of NLR on mRCC patients after surgery (Cetin et al, 2013;Lecot et al, 2019). As in ammatory immune cells, neutrophils alter the tumor microenvironment by expressing chemokine receptors CXCR1 and CXCR2 (Long et al, 2021). Moreover, neutrophils also release reactive oxygen species (ROS) and proteases to promote cancer development (Antonio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also pointed out the involvement of tumorassociated neutrophils (TAN) and tumor-associated macrophages (TAM) in maintaining the inflammatory or immunosuppressive TME that dictates the effect of therapies. [217][218][219][279][280][281][282][283][284][285][286] Neutrophils are the most abundant polymorph nuclear (PMN) cells available in the peripheral blood and early accumulated tumorassociated cells following therapies that make the inflammatory milieu. 280,[286][287][288][289][290] However, based on the tumor cell-secreted cy- including cell adhesion, directed migration, granule release, and superoxide production.…”
Section: Engineered Exosomes To Target Neutrophilsmentioning
confidence: 99%
“…[217][218][219][279][280][281][282][283][284][285][286] Neutrophils are the most abundant polymorph nuclear (PMN) cells available in the peripheral blood and early accumulated tumorassociated cells following therapies that make the inflammatory milieu. 280,[286][287][288][289][290] However, based on the tumor cell-secreted cy- including cell adhesion, directed migration, granule release, and superoxide production. 291 Although there are a few ligands that are an agonist for FPRs, we cannot utilize those for targeting neutrophils because they may stimulate the neutrophils for hyperfunctioning.…”
Section: Engineered Exosomes To Target Neutrophilsmentioning
confidence: 99%